Uji Validitas Dan Reliabilitas Kuesioner EQ-5D Bahasa Indonesia Untuk Pasien Hemodialisa Gagal Ginjal Kronik - Yugo Susanto; Riza Alfian; Zainur Rahim; Karani Karani (Jurnal Ilmiah Manuntung, 2018)
Chronic renal failure is a decrease in irreversible progressive renal function when the kidneys are unable to maintain a metabolic equilibrium. Chronic renal failure may impair the quality of life of patients it is necessary to measure the quality of life of patients with chronic renal failure. Measuring the quality of life of patients with chronic renal failure require a measuring instrument. One measure used is the instrument EQ-5D. This study aimed to find out the results of the validity and reliability of the instrument EQ-5D in patients with chronic renal failure. This study is an observational study conducted prospectively. Data were collected by questionnaire EQ-5D by all patients with chronic renal failure. The subjects were patients with chronic renal failure undergoing outpatient treatment at Hospital Ulin Banjarmasin period May - June 2017. Instrument EQ-5D in the analysis of the test reliability and validity test using test content validity. Subjects in this study amounted to 69 patients with chronic renal failure. This instrument is declared invalid as a result of content validity tested indicates the value of pearson correlation >0,23. While declared reliable because the Cronbach alpha values > 0,60. Questionnaire EQ-5D version of Indonesia has a valid and reliable so that it can be used to measure the quality of life of chronic renal failure hemodialysis patients.